Osmanlı Belgelerinde Alevilik İçin Kullanılan Dinî - Siyasî Tanımlamalar - Teber, Ömer Faruk (Dinî araştırmalar, 2007)
The usage of Alawism at present as an unbrella concept for the Rafizites, Babaites, Qalandars, Ishik, Qizilbashs and other mystic formations cited in the official correspondence (munshaat) of Ottoman period and written sources concerning its governmental ands social life raises some problems stemming from the misuse of concepts. In order to forestall this problem, the historical backgorunds of aforesaid concepts in the Otoman period will be analysed in this paper